Medical examinations within EU asylum procedures - Erick Vloeberghs; Evert Bloemen (Forced Migration Review, 2008)
The Care Full initiative – a joint project of Pharos, AmnestyInternational (Dutch section) and the Dutch Council forRefugees – seeks to create more awareness ofthe importance of medical considerations in theasylum procedure.